A. Djazuli's Thinking Regarding á¸¤ifáº“u al-Ummah: Dismissing the Entangled Bureaucracy to Commemorate the Era of Society 5.0 - Ahmad, Sabarudin; Anggraeni, Novita; Pambudi, Andrian Kukuh (De Jure: Jurnal Hukum dan Syari'ah, 2020)
Abstract: Nations in the world have been preoccupied with new ideas in the form of the society 5.0 era, while this nation is still trying to release the entangled bureaucracy. The government's efforts in reforming the bureaucracy with its various standards have not been able to produce satisfactory results. Therefore, this study seeks to contribute ideas by examining the thoughts of A. Djazuli about á¸¥ifáº“u al-ummah on this issue. This research is normative legal research. The analytical method used is the method of content analysis. The results of this study indicate that maqÄá¹£id syarÄ«Ê½ah has been oriented to individual problems, so that they pay less attention to humans in the community. á¸¤ifáº“u al-ummah as the development of maqÄá¹£id syarÄ«Ê½ah places this bureaucratic problem in the category of maqÄá¹£id al-hajiyat. The complicated bureaucracy does not damage human life but is very difficult. The bureaucratic system in Indonesia must be directed at a modern system with artificial intelligence in welcoming the era of 5.0 society.Keywords: bureaucracy; á¸¥ifáº“u al-ummah; era of society 5.0Abstrak:Bangsa-bangsa di dunia telah disibukkan dengan gagasan baru berupa era society 5.0, sedangkan bangsa ini masih berusaha melepaskan jeratan birokrasi yang berbelit. Upaya pemerintah dalam mereformasi birokrasi dengan berbagai standarisasinya belum mampu membuahkan hasil yang memuaskan. Oleh karena itu, penelitian ini berusaha memberikan kontribusi pemikiran dengan mengkaji pemikiran A. Djazuli tentang hifz al-ummah terhadap permasalahan ini. Penelitian ini merupakan penelitian hukum normatif. Metode analisis yang digunakan ialah metode analisis isi. Hasil penelitian ini menunjukkan bahwa maqashid syariah selama ini berorientasi pada persoalan individual, sehingga kurang memperhatikan manusia dalam komunitas. Hifz al-ummah sebagai pengembangan dari maqashid syariah menempatkan persoalan birokrasi ini dalam kategori maqashid al-hajiyat. Birokrasi yang berbelit tidak sampai merusak kehidupan manusia tetapi sangat menyulitkan. Sistem birokrasi di Indonesia harus diarahkan pada sistem modern dengan artificial intellegence dalam menyongsong era society 5.0.Kata Kunci: birokrasi; á¸¥ifáº“u al-ummah, era sosial Â 5.0